OPTIMISATION OF PARAMETERS AND OPERATING MODES OF AN IMPROVED TOOTH CULTIVATOR FOR PROCESSING COTTON ROW SPACINGS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In order to study the combined influence of the parameters of the improved tooth cultivator for processing cotton row spacings, which were studied in theoretical and single-factor experiments, on its performance indicators and to determine their optimal values, multifactor experiments were conducted using the mathematical planning method [1–2]. It was assumed that the influence of factors on the evaluation criteria was fully covered by a second-degree polynomial, and the experiments were conducted according to plan B5 [3–10].